2012
DOI: 10.1100/2012/474185
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Prognostic Value of Hypochloremia in Critically Ill Patients

Abstract: Little is known on the clinical effects of chloride on critically ill patients. We conducted this retrospective, observational study in 488 critically ill patients to investigate the incidence of chloride abnormalities, effects of hypochloremia in acid-base disorders, and association between chloride and clinical outcome. The study involved retrieval of arterial blood gas analyses, biochemical and demographical data from electrical records as well as quantitative acid-base analyses. For statistical analysis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 16 publications
4
72
0
1
Order By: Relevance
“…These studies showed conflicting results and included only a small number of patients with severe sepsis or septic shock. One study in 488 critically ill patients did not show an association between Cl and mortality (21). Notably, the hospital mortality rate in this study was only 3%, precluding the ability to establish a firm conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed conflicting results and included only a small number of patients with severe sepsis or septic shock. One study in 488 critically ill patients did not show an association between Cl and mortality (21). Notably, the hospital mortality rate in this study was only 3%, precluding the ability to establish a firm conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that hypochloremia, hyperchloremia, and dysnatremia are related to increased mortality (9)(10)(11). Nevertheless, identifying the Cl -:Na + ratio as a predictor of increased ICU mortality may be premature.…”
Section: Discussionmentioning
confidence: 99%
“…We think that this notion is most important in septic patients who have increased mortality. Rare combinations can be seen in daily clinical practice, and those combinations were also discussed in previous studies (Table 3) (6,9,13,(15)(16)(17)(18)(19). Kurt et al (15) indicated the presence of hypochloremic metabolic acidosis in 16% of acid-base disorders.…”
Section: Classification and Calculationsmentioning
confidence: 99%
See 2 more Smart Citations